Rekonstruksi Kedudukan Dokumen Elektronik sebagai Alat Bukti dalam Pembuktian Perkara Perdata Berbasis Deep Ecology: Rekonstruksi Kedudukan Dokumen Elektronik sebagai Alat Bukti dalam Pembuktian Perkara Perdata Berbasis Deep Ecology - Ariansyah; ES, Lucky Eka Khalis Aulia (Ikatan Hakim Indonesia (IKAHI), 2025)
The existence of electronic evidence, especially electronic documents, is a consequence of the development and sophistication of information and communication technology which can now be used in proving a case. The benefits of this research will get a reconstruction of the position of electronic documents as evidence in proving civil cases. The research method used is normative legal research method with legislation. The results of the study show the reconstruction of the existence of electronic evidence, especially electronic documents, can be used as letter evidence because currently any activity has carried the concept of paperless, so digital documents and electronic mail become vital, electronic evidence as part of efforts to support environmental sustainability by limiting the use of paper in the trial process. The legal basis and footing for the strength of electronic documents for evidentiary purposes in civil cases in accordance with the applicable procedural law is increasingly getting a place and flexibility, so there is no doubt that in defending arguments and rights in the civil field the existence of electronic documents is important and decisive. Electronic evidence in court proceedings is an attempt to contribute to ensuring environmental sustainability. This effort, in the eyes of environmental psychology, is a responsible attitude and behaviour towards environmental sustainability.